2022
DOI: 10.1016/j.cub.2021.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia disrupts distance, but not direction, of path integration memory

Abstract: Highlights d Anesthetizing ants affects their path integration memory d Anesthesia degrades the distance, but not the direction, memory of the ants d The same effect is replicated by a path integration model of the central complex d The results argue against recurrently maintained activity as the memory substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…As in previous studies of insect path integration following chill-coma anesthesia, the orientations of homeward paths following anesthesia were maintained. Although in ants 52 and dung beetles 53 the distances of home vectors were diminished after cooling, these distances were approximately correct across all manipulations in our experiments, suggesting very stable vector memories, potentially due to a long-term storage mechanism of home vector memories in bumblebees. However, experiments with ants revealed that these insects are able to correctly home after anesthetization, but only if they are in a familiar environment containing landmarks.…”
Section: Discussionmentioning
confidence: 55%
“…As in previous studies of insect path integration following chill-coma anesthesia, the orientations of homeward paths following anesthesia were maintained. Although in ants 52 and dung beetles 53 the distances of home vectors were diminished after cooling, these distances were approximately correct across all manipulations in our experiments, suggesting very stable vector memories, potentially due to a long-term storage mechanism of home vector memories in bumblebees. However, experiments with ants revealed that these insects are able to correctly home after anesthetization, but only if they are in a familiar environment containing landmarks.…”
Section: Discussionmentioning
confidence: 55%
“…The motor noise level was modelled as a decaying exponential function of the memory amplitude, as in Pisokas et al (2021). The memory amplitude a m was defined as the difference between the maximum and minimum value along the sinusoidal pattern of memory unit values (Pisokas et al, 2021). where y max is the maximum motor noise level (corresponding to zero vector ant paths), and s m is the slope of the exponential function.…”
Section: Methodsmentioning
confidence: 99%
“…The translational velocity of the simulated agents during homing was iteratively updated using the formula where v ( t ) is the agent’s velocity at time step t, a = 0.08 m / s 2 is an acceleration constant, Δ t is the simulated time step duration, and µ f = 0.15 is a friction constant. The velocity was reset to 0 m / s whenever the agent performed a turn larger than 20 ° simulating a stop on turning as observed in ants (Pisokas et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations